The global aerosol-climate model ECHAM-HAM, version 2: sensitivity to improvements in process representations - Zhang, K; O'Donnell, D; Kazil, J; Stier, P; Kinne, S; Lohmann, U; Ferrachat, S; Croft, B; Quaas, J; Wan, H; Rast, S; Feichter, J (2012)
This paper introduces and evaluates the second version of the global aerosol-climate model ECHAM-HAM. Major changes have been brought into the model, including new parameterizations for aerosol nucleation and water uptake, an explicit treatment of secondary organic aerosols, modified emission calculations for sea salt and mineral dust, the coupling of aerosol microphysics to a two-moment stratiform cloud microphysics scheme, and alternative wet scavenging parameterizations. These revisions extend the model's capability to represent details of the aerosol lifecycle and its interaction with climate. Nudged simulations of the year 2000 are carried out to compare the aerosol properties and global distribution in HAM1 and HAM2, and to evaluate them against various observations. Sensitivity experiments are performed to help identify the impact of each individual update in model formulation. Results indicate that from HAM1 to HAM 2 there is a marked weakening of aerosol water uptake in the lower troposphere, reducing the total aerosol water burden from 75 Tg to 51 Tg. The main reason is the newly introduced κ-Köhler-theory-based water uptake scheme uses a lower value for the maximum relative humidity cutoff. Particulate organic matter loading in HAM2 is considerably higher in the upper troposphere, because the explicit treatment of secondary organic aerosols allows highly volatile oxidation products of the precursors to be vertically transported to regions of very low temperature and to form aerosols there. Sulfate, black carbon, particulate organic matter and mineral dust in HAM2 have longer lifetimes than in HAM1 because of weaker in-cloud scavenging, which is in turn related to lower autoconversion efficiency in the newly introduced two-moment cloud microphysics scheme. Modification in the sea salt emission scheme causes a significant increase in the ratio (from 1.6 to 7.7) between accumulation mode and coarse mode emission fluxes of aerosol number concentration. This leads to a general increase in the number concentration of smaller particles over the oceans in HAM2, as reflected by the higher Ångström parameters. Evaluation against observation reveals that in terms of model performance, main improvements in HAM2 include a marked decrease of the systematic negative bias in the absorption aerosol optical depth, as well as smaller biases over the oceans in Ångström parameter and in the accumulation mode number concentration. The simulated geographical distribution of aerosol optical depth (AOD) is better correlated with the MODIS data, while the surface aerosol mass concentrations are very similar to those in the old version. The total aerosol water content in HAM2 is considerably closer to the multi-model average from Phase I of the AeroCom intercomparison project. Model deficiencies that require further efforts in the future include (i) positive biases in AOD over the ocean, (ii) negative biases in AOD and aerosol mass concentration in high-latitude regions, and (iii) negative biases in particle number concentration, especially that of the Aitken mode, in the lower troposphere in heavily polluted regions. © 2012 Author(s).